Analisis Faktor-Faktor yang Mempengaruhi Partisipasi Sukarela Siswa dalam Layanan Bimbingan dan Konseling di SMAS Sinar Husni Labuhan Deli - Widya, Widya Lestari; Khairuddin Tambusai (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
This study aims to identify and analyze the factors influencing students’ voluntary participation in utilizing guidance and counseling (BK) services at SMA Swasta Sinar Husni Labuhan Deli. Data were collected through observations, in-depth interviews with students and BK teachers, as well as document analysis, and were analyzed using qualitative techniques. The findings show that the BK teacher’s warm, empathetic, open, and non-judgmental personality is the main factor encouraging students’ voluntary participation. An interpersonal approach based on emotional closeness—including the use of the affectionate term “bunda,” which reflects local Malay culture—helps build students’ sense of safety and trust. Spiritual-based educational strategies, such as assigning students to recite short surahs or perform dhuha prayers, also contribute to transforming the image of BK services from a disciplinary space into a space for personal development and growth. These findings highlight that the BK teacher’s personality and an egalitarian relational approach play a vital role in creating a supportive, inclusive, and humanistic atmosphere, thereby enhancing students’ voluntary participation in BK services.